STM32-Based Health Monitoring System - Chen, Huixian; Cheng, Tianqi; Zhu, Zidi; Mai, Huanxiao (International Journal of Mechanical and Electrical Engineering, 2025)
With the intensifying trend of global population aging, the demand for health monitoring among the elderly is becoming increasingly urgent. This paper addresses the issues of bulkiness and complexity in traditional health monitoring devices by proposing a portable health monitoring system based on STM32 embedded technology. The system utilizes the MAX30102 photoplethysmography (PPG) sensor to achieve non-invasive heart rate and blood oxygen saturation (SpO₂) detection. An optimized signal processing algorithm effectively eliminates motion artifacts, while the STM32F103C8T6 microcontroller facilitates data acquisition and real-time analysis. Compared to conventional medical equipment, this system is compact, energy-efficient, and user-friendly, offering a reliable technological solution for daily health monitoring and chronic disease management in the elderly. It holds significant application value in the field of smart elderly care.